Human mesostriatal response tracks motivational tendencies under naturalistic goal conflict. Issue 6 (1st February 2016) - Gonen, Tal; Soreq, Eyal; Eldar, Eran; Ben-Simon, Eti; Raz, Gal; Hendler, Talma
Abstract: Goal conflict situations, involving the simultaneous presence of reward and punishment, occur commonly in real life, and reflect well-known individual differences in the behavioral tendency to approach or avoid. However, despite accumulating neural depiction of motivational processing, the investigation of naturalistic approach behavior and its interplay with individual tendencies is remarkably lacking. We developed a novel ecological interactive scenario which triggers motivational behavior under high or low goal conflict conditions. Fifty-five healthy subjects played the game during a functional magnetic resonance imaging scan. A machine-learning approach was applied to classify approach/avoidance behaviors during the game. To achieve an independent measure of individual tendencies, an integrative profile was composed from three established theoretical models. Results demonstrated that approach under high relative to low conflict involved increased activity in the ventral tegmental area (VTA), peri-aquaductal gray, ventral striatum (VS) and precuneus. Notably, only VS and VTA activations during high conflict discriminated between approach/avoidance personality profiles, suggesting that the relationship between individual personality and naturalistic motivational tendencies is uniquely associated with the mesostriatal pathway. VTA–VS further demonstrated stronger coupling during high vs low conflict. These findings are the first to unravel the multilevel relationship among personality profile, approach tendencies in naturalistic set-up and their underlying neural manifestation, thus enabling new avenues for investigating approach-related psychopathologies.